Penguatan Pendidikan Berbasis Pancasila dalam Meningkatkan Literasi Digital Mahasiswa di Era Digitalisasi Nasional di Universitas Jember - Saphira, Refiana Aurelia; Ratna Endang Widuatie; Dania Nur Kamila; Natasya Az Zahra Ardiansyah; Yunan Gahral; Maisyithah Alifiyah Sabila Rohmah (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Strengthening Pancasila-based education at the University of Jember is a strategic step in facing the challenges of the national digitalization era. Through a learning approach that instills moral, social, and national values, students are guided to develop ethical, critical, and responsible digital literacy skills. This research employed qualitative methods, including literature review techniques and observations of educational programs at UNEJ. The results indicate that integrating Pancasila values into the learning process strengthens students' character as agents of social change who are adaptive to technological developments. The implementation of Pancasila-based education also encourages collaboration, mutual cooperation, and social awareness in the digital world. Therefore, strengthening Pancasila-based education is a crucial foundation for creating a young generation with character, digital literacy, and global competitiveness without losing their identity as Indonesians.